Potential of real-time PCR threshold cycle (CT) to predict presence of free toxin and clinically relevant C. difficile infection (CDI) in patients with cancer. Issue 4 (April 2018) - Kamboj, Mini; Brite, Jennifer; McMillen, Tracy; Robilotti, Elizabeth; Herrera, Alejandro; Sepkowitz, Kent; Babady, N. Esther
Highlights: CDI is a toxin-mediated disease. qPCR threshold cycle (CT ) may predict the presence of toxin and CDI severity. A CT of 28.0 (using cell culture toxin assay as reference) predicted 77% cytotoxin positive cases. A CT of 28.0 predicted 91% and 100% of severe and complicated CDI cases respectively. Abstract: Objectives: Clostridium difficile infection (CDI) is a toxin-mediated disease. Oncology patients are at increased risk for developing CDI. Diagnosis of CDI by PCR has led to misclassification of some C. difficile carriers as CDI cases. We determined if an optimized C. difficile PCR cycle threshold value (CT ) could reliably predict presence of free toxin, and in turn improve the utility of PCR in detecting clinically relevant CDI in oncology patients. Methods: 183 consecutive patients positive for C. difficile by the Xpert C. difficile were additionally tested using the cell culture cytotoxicity neutralization assay (CYT) and enzyme immunoassays (EIA). CT values at diagnosis and relevant clinical information were recorded. Receiver operating characteristic (ROC) curve was used to assess predictive validity and to find optimal CT for CYT positive cases. Severity of CDI was assessed by blinded charts review. Results: Using CYT as the reference, ROC-derived Youden cut-off CT of 28.0 predicted 77% cytotoxin positive cases, and 91% and 100% of severe and complicated CDI episodes respectively. The median CT values for non-severe, severe, and complicated CDI episodes were 28.0, 24.5 and 22.5 respectively (p = 0.005). Conclusions: Lower CT value of the Xpert C. difficile PCR was associated with the presence of toxin and increased CDI severity. CT values may be beneficial in interpreting positive C. difficile PCR results.